Implementing gender transformative approaches (GTAs) in smallholder chicken value chains in Tanzania - Achandi, Esther L.; Galiè, Alessandra; Jumba, Humphrey; Jeremiah, Adolf; Campbell, Zoë A.; Omore, Amos O. (International Livestock Research Institute, 2025)
Inequitable gender norms hinder the development of efficient and equitable agri-food systems. In chicken value chains, for example, inequitable gender norms, inhibit the ability of women smallholder farmers to engage in and benefit from chickens limiting the potential of the sector for supporting rural livelihoods and women’s empowerment. Gender transformative approaches (GTAs) have been used in different contexts to address restrictive gender norms and empower women. However, the processes to identify relevant norms and develop appropriate GTAs in agri-food systems, are still being developed and scrutinized. In this brief, we outline the implementation of GTAs to address restrictive gender norms adopted by the International Livestock Research Institute (ILRI) in smallholder chicken value chains in recent years. We highlight the engagement of target communities in participatory processes of research to uncover the restrictive gender norms to target, intervention formulation and implementation and a post intervention exploratory study to enlist community feedback and identify how to improve the intervention for higher possibilities of changes in restrictive gender norms.